Anti-Yo Associated Paraneoplastic Cerebellar Degeneration in a Man with Large Cell Cancer of the Lung - Linda Hasadsri; James Lee; Bonnie H. Wang; Lalitha Yekkirala; Mingtao Wang (Case Reports in Neurological Medicine)
Purkinje cell cytoplasmic antibody type 1 (PCA-1), or anti-Yo, is the most frequently detected autoantibody in paraneoplastic cerebellar degeneration (PCD). The vast majority of cases of anti-Yo PCD, however, occur in females over 60 years old and are associated with gynecologic tumors. Only 10 cases have been reported in males, and only 2 were associated with cancer of the lung. Here we describe the youngest known case of PCA-1 positive PCD in a male, whose lung tumor was undetectable even on FDG-PET.